Influence of Extract Swiftlet Nest (Collocalia Fuciphago) as Antihyperglycemia to Circulating Endothelial Cells in Rat (Rattus novergicus) Induced by Streptozotocin - Francisca Diana Alexandra; Satriyandi M; Agnes Frethernety; Triawanti Triawanti (Berkala Kedokteran, 2018)
Abstract: Hyperglycemia could increase the oxidative stress by catalyzes the formation of free radical as anion superoxide(O2-). Oxidative stress will effect in endothelial damaged. This study aimed to evaluated the influence of  extract swiftlet nest  (Collocalia fuciphago) to glucose level and  CEC in rat (Rattus novergicus). Rats were classified into 4 groups, there were control group (K) and 3 treatments group (dose 1; 10 and 100 mg / kgBW) The seventh day  after induced by Streptozotozin (i.p),  the rats  had increased  glucose ± 102 – 108 mg/dL, then treated  with the  extract of   Swiftlet  nest for 28  days  by  oral.  The CEC was measured by Hladovec method. The results showed  the blood glucose level were significant differences ( p = 0.035). The number of CEC decrease significantly (p=0,002). In  conclusion  that extract of Swiftlet  nest  can effect  to decrease  glucose level and CEC number in plasma rat (Rattus novergicus) Keywords: Hyperglycemia, Circulating Endothelial Cells, Collocalia fuciphago